Strategi Politik Partai Golkar Pada Pemilihan Umum Kepala Daerah Kabupaten Karanganyar Tahun 2013 - Dian Pratiwi; Susuilo Utomo; Fitriyah . (Journal of Politic and Government Studies, 2014)
This study analyzes the political strategies used by the Golkar Party in the elections of regional heads in Karanganyar. In the regional head elections in 2008, which is carried by the Golkar candidate, namely Juliyatmono-Sukismiyadi, defeat of incumbent Rina Iriani-Paryono. In 2008, incumbent is more popular and higher electability than Juliyatmono. In the regional head elections in 2013, Golkar brought back Juliyatmono and accompanied by a cadre of the Partai Keadilan Sejahtera (PKS), Rohadi Widodo. Then, how the Golkar Party's political strategy in the elections of regional heads in 2013 to be able to win the vote? Moreover, the regional head elections in 2013 no incumbent Rina Iriani figure ever beat Juliyatmono. In this study, researchers used a qualitative approach that will yield descriptive data. The research was conducted in Karanganyar. The data were obtained through observation, interviews with Juliyatmono as Chairman of the Golkar Party Regional Leadership Council and elected Regent Karanganyar, winning team, and the Golkar Party’s cadres are able to provide information, and data from the document.Political strategies used Golkar Party in the elections of regional heads Karanganyar in 2013 done in the form of the election campaign strategy, career,2mass mobilization, coalition, development and empowerment of political parties, the public, approaches and political communication. The success of this political strategy capable of winning a couple Juliyatmono-Rohadi Widodo (Yuro) with 243 168 votes. Yuro pair beat a couple Paryono-Dyah Shintawati (Pasti) who obtained 197 316 votes and partner Aris-Wagiyo (Ayo) gained 32,212 votes. Key words: Regional Head Election, Golkar Party, Political Strategy